Development and Utilization of an Isolation Box Test to Characterize Personality Traits of Dairy Calves - Woodrum Setser, Megan M.; Neave, Heather W.; Vanzant, Eric; Costa, Joao H. C. (Frontiers in Animal Science, 2022)
The use of an isolation box test (IBT) to characterize personality traits has been used in non-bovine species with success. We aimed to develop an IBT for dairy calves and determine if the behavioral responses to an IBT were associated with personality traits found from traditional tests (novel person, novel object, and a startle tests) and average daily gain (ADG; Kg/d) through weaning. Calf movement while in the IBT was measured via accelerometers attached to 5 locations on the exterior of the box. A total movement index (TMI) was calculated based on accelerometer readings during the IBT. We performed a principal component analysis on the traditional tests and identified 3 influential factors that we labeled as “fearful,” “bold,” and “active”. Calves were weighed biweekly to track liveweight ADG. Factor scores and ADG were regressed against TMI. A significant negative association was found between the TMI and the factor “active”, indicating the validity of IBT as a tool for assessing personality traits of dairy calves. Furthermore, TMI had a positive association with ADG through the entire experimental period and thus has potential to help predict performance through weaning. IBT has potential to be used as a personality test in research scenarios. Further development is needed to produce an IBT that would be appropriated to measure animals’ responses reliably in production settings. An automated test that can accommodate a wide range of ages and developing a computer learning model to interpret output from the IBT would be a possible option to do so.